2017
DOI: 10.3390/rs9030275
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Mass Loss during the 1960s and 1970s in the Ak-Shirak Range (Kyrgyzstan) from Multiple Stereoscopic Corona and Hexagon Imagery

Abstract: Abstract:Comprehensive research on glacier changes in the Tian Shan is available for the current decade; however, there is limited information about glacier investigations of previous decades and especially before the mid 1970s. The earliest stereo images from the Corona missions were acquired in the 1960s but existing studies dealing with these images focus on single glaciers or small areas only. We developed a workflow to generate digital terrain models (DTMs) and orthophotos from 1964 Corona KH-4 for an ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 50 publications
(91 reference statements)
2
35
0
Order By: Relevance
“…The large surface lowering visible in the upper part of the accumulation regions which continue to the non‐glacierised areas (Figure (A), (B), d) stem from errors in the DEMs. These areas are at the edges of individual Corona DEMs that were mosaicked to a single DEM (Goerlich et al, ), and as such some erroneous elevation values are to be found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The large surface lowering visible in the upper part of the accumulation regions which continue to the non‐glacierised areas (Figure (A), (B), d) stem from errors in the DEMs. These areas are at the edges of individual Corona DEMs that were mosaicked to a single DEM (Goerlich et al, ), and as such some erroneous elevation values are to be found.…”
Section: Resultsmentioning
confidence: 99%
“…Three stereo pairs of Corona KH‐4A data acquired in November 1964 were used to generate a DEM with a resolution of 10 m and subsequent orthoimages using the Remote Sensing Software Graz (RSG) (cf. Goerlich et al, ). The quality of the DEMs was promising, but problems occurred especially in areas with low contrast such as steep slopes in shadow and bright snow covered areas, especially with the KH‐4A DEM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMB was measured intensively from 1967 to 1998 (Suslov et al, 1980;Glazirin et al, 1993) and the monitoring was re-established in 2011 . Since then, annual glaciological surveys were continuously carried out in late August.…”
Section: Abramov Glaciermentioning
confidence: 99%
“…Furthermore, other authors focused on selected regions of the central and northern Tien Shan (e.g. Aizen et al, 2007;Pieczonka et al, 2013;Pieczonka and Bolch, 2015;Goerlich et al, 2017), deriving glacier-specific geodetic mass balances. These studies often cover large areas, but temporal resolution is typically limited to 5 years or longer periods.…”
Section: Introductionmentioning
confidence: 99%